Tjiptojuwono, Eko ANALISIS PENGENDALIAN SISTEM INFORMASI AKUNTANSI PIUTANG (JBT (JURNAL BISNIS dan TEKNOLOGI), 2017)
This research was conducted to analyzed element of account receivables accounting information system control. The method of data collection in this final project uses interviews method that produces documents from PT. Transindra Perkasa as research object. The results of this research shows that the accounting information system does not meet element of management information system controls. Element of management information system controls which used on this reasearch are management control to account receivable information system conducted to operational function, and recording function. The result of this research are there is uneffective organizational structure with positional capture which implicated to controlless, and urecorded document which implicated to miss information. Recomendation from this research are restructuring orgnization to optimize controling, and optimizing document recording.